A simple and sensitive fluoroimmunoassay based on the nanobody-alkaline phosphatase fusion protein for the rapid detection of fenitrothion - Chen, Zi-Jian; Huang, Ai-Jun; Dong, Xiu-Xiu; Zhang, Yi-Feng; Zhu, Lin; Luo, Lin; Xu, Zhen-Lin; Wang, Hongwu (Frontiers in Sustainable Food Systems, 2023)
Abstract: Immunoassay is a powerful tool for the rapid detection of small harmful organic molecules. In this work, a simple and sensitive fluoroimmunoassay (FIA) based on nanobody-alkaline phosphatase fusion protein (VHHjd8-ALP) and blue-emissive carbon dots (bCDs) was developed for the rapid detection of fenitrothion. The bCDs was synthesized by using the one-step hydrothermal method. The citric acid and urea were used as carbon and nitrogen source, respectively. The synthesized bCDs were characterized by fluorescence spectrum, high-resolution transmission electron microscopy, X‐ray photoelectron spectroscopy and Fourier transform infrared spectroscopy. After one step competitive immunoassay, the VHHjd8-ALP bound to microplate catalyzed the substrate p-nitrophenylphosphate (pNPP) into p-nitrophenol (pNP), the later can quench the blue of bCDs due to inner-filter effect. After condition optimization, a FIA calibration curve was finally created, which showed a IC50 value of 16.25 ng/mL and the limit of detection (LOD) of 0.19 ng/mL. Compared with the pNPP-based one-step conventional indirect competitive enzyme-linked immunoassay (icELISA), the developed FIA showed 11-fold sensitivity improvement. Furthermore, the analysis period of FIA only takes approximately 55 min, which was obvious faster than that of the conventional icELISA. The recovery test showed the recoveries from 81.8% to 119% with fruits and vegetable samples, which verified the practicability and accuracy of the developed FIA.